MANAJEMEN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA SISWA DI MAN KISARAN - S Syafaruddin; Hadi Akmal Lubis; Ahmad Taufik Al-Afkari Siahaan (Jurnal Al-Fatih, 2018)
This research describes how management library in improving student reading interest in the MAN range. The purpose of this research is to know the: (1) planning the library in improving student reading interest, (2) organizing the library in improving student reading interest, (3) the implementation of the program library in increasing interest in reading (4) the supervision of library in increasing interest in reading. This study uses qualitative methods, because it is intended to explain the behaviour of the head of the madrasa, the head of the library, teachers, and students in the implementation of the management of the library to improve the reading interests of students. Data collection techniques used consisted of interviews, observation and study of the document. While the data analysis was done with the reduction of data, exposure data and the withdrawal of the conclusion. The findings of this research there are four, namely: first; Planning Library in improving student reading interest in the MAN Range involving the head of the madrasa, the Committee, head of libraries, librarians, and students. Such personnel collaborated in planning the program library, with the purpose of preparing a guide to activities to avoid errors and unintended failure in determining a plan library as well as to increase the effectiveness and efficiency in their implementation. Second; Organizing library MAN Range is done by creating an organizational structure and Division of tasks Library Manager library, in accordance with their respective personal ability and has never followed a training library. The third; The implementation of the program library in improving student reading interest in the MAN Range is done after the process of planning and organizing library along with the staff of the library has been the realization of a variety of programs it works with full commitment and responsibility. The implementation of the programme of work perpustakaanpengaturan hours of compulsory reading for students of every class have been scheduled every week, program services read the book and borrow a book in the library will receive rewards or awards. Fourth; The supervision of library in improving student reading interest carried the head of the Madrasa, the caretaker Committee, head of the library. This form of surveillance carried out in accordance with the basic tasks and functions, by monitoring and evaluating the results of the performance of the head library mainly ketercapaian work programme library.